2010
DOI: 10.17221/1773-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heavy metals on soil respiration during decomposition of sugarcane (Saccharum officinarum L.) trash in different soils

Abstract: An experiment was conducted to study the effect of heavy metals (Cd, Cr and Pb), soil texture (sandy, loam and clay) and incubation periods (7, 15, 30, 60, 90 and 120 days) on soil respiration (CO 2 evolution) during sugarcane trash decomposition in laboratory conditions of the Indian Institute of Sugarcane Research, Lucknow, India. Surface soils (0-15 cm) were collected from agricultural fields and crop residue of sugarcane trash (Saccharum officinarum L.) was taken in the institute farm. Crop residue (10 t/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
(17 reference statements)
3
4
0
Order By: Relevance
“…observed that addition of Si at 400 mg Si kg −1 (as This study also showed that soil respiration (CO 2 evolution) decreased with increasing Cd concentrations in soil which indicates that Cd has a toxic effect on microbial respiration. Similar of our result was observed by other investigators [35] [36]. Verma et al [36] found soil respiration (CO 2 evolution) significantly decreased in Cd contaminated soils compared to uncontaminated soils.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…observed that addition of Si at 400 mg Si kg −1 (as This study also showed that soil respiration (CO 2 evolution) decreased with increasing Cd concentrations in soil which indicates that Cd has a toxic effect on microbial respiration. Similar of our result was observed by other investigators [35] [36]. Verma et al [36] found soil respiration (CO 2 evolution) significantly decreased in Cd contaminated soils compared to uncontaminated soils.…”
Section: Discussionsupporting
confidence: 93%
“…Similar of our result was observed by other investigators [35] [36]. Verma et al [36] found soil respiration (CO 2 evolution) significantly decreased in Cd contaminated soils compared to uncontaminated soils. The addition of lherzolite to the soil diminished the inhibitory effects of Cd on biological parameters and hence enhanced soil respiration.…”
Section: Discussionsupporting
confidence: 93%
“…Cd addition in this study reduced Rs, and the cumulative CO 2 efflux of the Cd treatment was 19% lower than that of the controls (Figure 4b,c), which agrees with several previous studies [46,47]. Rs primarily reflects plant root respiration and microbial respiration [48].…”
Section: Effect Of CD Addition On Rssupporting
confidence: 92%
“…The parameters observed in this experiment were: (1) plant height (cm) at 6 WAP; (2) leaf number (blade) at 6 WAP; (3) leaf greenness with chlorophyll meter (SPAD value) at 8 WAP; (4) total chlorophyll content (mg/g fresh weight) and β-carotene content (μmol/g) (modified procedure from Lobato et al (2010)); (5) maximum K vegetative leaf absorption (formula: nutrient content of sweet corn leaves (%) x dry weight (g)); (6) dry weight (g); (7) row length (cm); (8) number of rows per ear (row); (9) total production (t/ha); (10) soluble solids (°Brix) at days 70, 73 and 75 DAP measured by refractometer; (11) soluble solids loss (%); (12) respiration of the soil (mg/h/m 2 ) at 0, 15, 30, 45, 60 and 70 DAP by a modified Verstraete method (Verma, Yadav, Singh, Suman, & Gaur, 2010); and (13) number of microbial populations (10 -8 cfu/ml) at 0, 30 and 70 DAP assessed via the agar cup method (Upadhyay et al, 2016).…”
Section: Methodsmentioning
confidence: 99%